Representasi Kekerasan Dalam Film Rumah Untuk Alie: Analisis Semiotika Barthes - Julian Mega Berliana; Intan Leliana; Laurensia Retno Hariatiningsih (Journal of Innovative and Creativity, 2025)
This research aims to analyze the representation of violence in the film Home for Alie using Roland Barthes' semiotic theory. The method used is a qualitative approach with semiotic analysis which focuses on three levels of meaning, namely denotation, connotation and myth. The research results show that the film represents various forms of violence, both physical, verbal and psychological, through visual and verbal signs. Violence is not only presented as a visible event, but also contains ideological meaning that reflects power relations, patriarchal structures and social construction within the family. These findings confirm that film as mass media has an important role in shaping public perceptions, reproducing cultural values, and increasing critical awareness of the issue of domestic violence. Thus, Rumah untuk Alie not only functions as entertainment, but also as a reflective and educational medium in voicing social issues